22nd EAA Congress – 15th ISGA Congress – 5th International Conference of Evolutionary Medicine - Tutkuviene, Janina; Cameron, Noel; Jakimaviciene, Egle Marija; Janulioniene, Rasa (Vilnius University Proceedings, 2022)
This Abstract book covers material of the Joint International Meeting: 22nd EAA Congress, 15th ISGA Congress, 5th International Conference of Evolutionary Medicine. This event was organized at Vilnius University (Lithuania) in 2022 on August 24-27th in a hybrid way, which brought together 28 famous keynote speakers from Austria, Great Britain, the USA, Australia, Croatia, Poland, France, Switzerland, Germany and other countries. This book includes the abstracts of more than 180 presentations.The main theme of the 22nd Congress of EAA (European Anthropology Association) is Human variation and adaptation in a changing world with a particular focus on physical, biopsychosocial and general health changes in the human body. The topics of the 15th Congress of ISGA (International Society for the Study of Human Growth and Clinical Auxology) expand our understanding of human growth and development in health and disease. Special attention is paid to human growth in the period of early ontogenesis, to environmental factors affecting growth (including growth in war and other stressful conditions), children and adolescents’ nutrition and body composition, also modern analyses of growth data. The 5th International Conference on Evolutionary Medicine expands an interdisciplinary approach to understanding the diversity of human health and disease, sharing research from different fields to cooperate together in order to understand the mechanisms of different disease from the evolutionary point of view.The Abstract Book of this joint international event should not only be interesting to scientists of various scientific fields such as anthropology, human biology, public health, and health education, but also to clinical doctors, especially neonatologists, paediatricians, family practitioners and many others. Organisers believe that knowledge of the potential of human adaptation and evolutionary mechanisms in maintaining the health and wellbeing of our species will encourage fruitful interdisciplinary discussions in medical society as well as among biologists, sociologists and other specialists.
Keywords: European Anthropology Association; International Society for the Study of Human Growth and Clinical Auxology; International Conference on Evolutionary Medicine; Congress; Faculty of Medicine; Vilnius University